High-tech cycling - Burke, Edmund R., 1949-2002 (Champaign, Ill. : Human Kinetics, 2003)
Offering clear explanations and practical applications for cutting edge science, this book details critical performance issues for both road and mountain biking. The scientific justification for equipment positioning and training decisions is explained, illuminating the human-technology interface. The newest edition of "High-Tech Cycling" picks up where the first edition left off, incorporating the most current information on cycling technology, technique, physiology, and mechanics in one comprehensive book. Thorough explanations, along with supportive graphs and illustrations, give you an in-depth understanding of the dynamics between human and machine that combine to create champions of the sport. Thirteen experts contributed to this book, compiling the latest scientific information available to enhance your cycling performance. From bike optimization to body positioning, "High-Tech Cycling" provides the details you want, including new information you won't find in any other book. With each chapter, you'll gain fresh insights and new information from another research insider. In "High-Tech Cycling," you'll learn more than what to do and how to do it; you'll discover the scientific justification for equipment, positioning, and key training decisions. The book covers every aspect of the cycling world, from racing on the road to specific elements of mountain biking. "High-Tech Cycling" cuts through opinions and misinformation to give you the cutting edge on the science behind the sport. From heart rate monitors and altitude tents to power hubs, suspension systems, frame construction, pedaling efficiency, and beyond, the book covers every aspect of technology and technique. Additional chapters are dedicated to nutrition, altitude training, and the physiological demands of the sport.
Selecting cycling equipment / Chester R. Kyle -- Bicycle suspension systems and mountain bike technology / John Olsen -- Body positioning for cycling / Edmund R. Burke and Andrew L. Pruitt -- Optimizing the crank cycle and pedaling cadence / Alejandro Lucía, Conrad Earnest, Jesús Hoyos, and José L. Chicharro -- Cycling biomechanics: road and mountain / Jeffrey P. Broker -- Cyling power: road and mountain / Jeffrey P. Broker -- The cycling world hour record / Chester R. Kyle and David R. Bassett, Jr. -- Altitude training in preparation for competition at sea level / Randall L. Wilber -- Nutrition for competitive cycling / Asker E. Jeukendrup -- Physiology of professional road cycling / Alejandro Lucía, Jesús Hoyos, and Jose L. Chicharro -- Physiology of mountain biking / Holden S-H. MacRae.
Includes bibliographical references and index.
Keywords: Wielersport; Cycling